UMPSA researchers share expertise in IoT systems and fertigation for farmers in Pahang - Nur Hazuani, Nasaruddin (UMPSA, 2023)
PEKAN, November 22, 2023 – A team of researchers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) shared their expertise in the IoT-Based Smart Farming System project.